Provider Attitudes, Organizational Readiness for Change, and Uptake of Research Supported Treatment - Bornheimer, Lindsay A.; Acri, Mary; Parchment, Tyrone; McKay, Mary M. (Research on Social Work Practice, 2019)
Purpose:As implementation and evaluation of research supported treatment (RST) expands across diverse mental health settings, it is essential to understand the facilitators and inhibitors of uptake. The current study examined the relationships between organizational readiness for change, attitudes toward RST, and use of RST among a sample primarily of social workers.Methods:Participants included 158 providers from public child mental health outpatient clinics in the New York metropolitan area. Data were analyzed using structural equation modeling.Results:Use of RST was greater among providers who were younger and had fewer years of professional experience. Both organizational need for change and climate directly and indirectly related to use of RST through attitudes toward RST (partial mediator).Discussion:The organizational context is an important factor that relates to attitudes toward and use of RST in practice. Future research is needed to continue examining factors of RST uptake and sustainability.
3 citations (Crossref) [2023-10-31]
Keywords: dept.swk; organizational readiness for change; provider attitudes; research supported treatment; treatment uptake

Retooling the health care workforce in the era of the Affordable Care Act: An evaluation of an advanced certificate program in integrated primary and behavioral health care - O’Brien, Kyle H.; Acri, Mary C.; Campanelli, Peter C.; Cerniglia, Joseph A.; McKay, Mary M. (Journal of Teaching in Social Work, 2018)
The Affordable Care Act aims to increase affordable coverage, reduce overall costs, and improve health outcomes. To achieve these aims, new knowledge and skills must be built within the existing workforce. The purpose of this article is to examine the behavioral and organizational changes brought about by an educational program that aimed to retool the healthcare workforce for the implementation of integrated primary and behavioral healthcare models, with an added emphasis on prevention. Sixty-three participants of an Advanced Certificate Program completed 1 or more evidence-informed learning modules centered on integrated primary and behavioral health care. The vast majority of students who completed each of the 5 modules of the program reported acquiring new knowledge and skills. Student satisfaction of the program met or exceeded overall expectations. In addition, program participation has resulted in not only students’ intentions to change workplace practices but also actual implementation of workplace changes related to integrated care models. The Advanced Certificate Program appears to be a promising platform for service providers to align their knowledge and skills with the premises of current healthcare reform. © 2018, © 2018 Taylor & Francis.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/025-288-723-272-601, pop00087 tex.type: [object Object]
Keywords: Affordable Care Act; Integrated primary and behavioral health care; certificate programs; dept.rec; dept.swk; integrated care; peer-reviewed; workforce training

Barriers and facilitators to mental health screening efforts for families in pediatric primary care - Acri, Mary; Zhang, Shirley; Chomanczuk, Aminda H.; O’Brien, Kyle H; De Zitella, Maria L. Mini; Scrofani, Paige R.; Velez, Laura; Garay, Elene; Sezer, Sara; Little, Virna; Cleek, Andrew; McKay, Mary M (Journal of Family Social Work, 2018)
The purpose of this commentary was to describe the barriers and facilitators to mental health screening efforts for children between age 5 and 18 years within three primary care clinics in poverty-impacted communities as part of an integrated care model. Three screeners, two women and one male, participated in a screening effort between September and December 2015. Screeners were interviewed about their perceptions of barriers and facilitators to screening. Organizational, family, and screener-level factors were found to influence delivery of screenings to children. Given the benefits of screening in primary care settings, identifying barriers to these initiatives and ways to address them pre-emptively could potentially alter the developmental trajectory and outcomes of children at risk for serious mental health conditions. © 2018, © 2018 Taylor & Francis.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/104-082-353-634-694, pop00286 tex.type: [object Object]
Keywords: Screening and detection efforts; article; case report; child; child mental health; clinical article; dept.rec; dept.swk; female; human; human experiment; integrated care; male; mental health; outcome assessment; peer-reviewed; perception; poverty; primary medical care